Improving Organizational Culture to Increase Job Satisfaction and Performance in Operational Management of MSMEs - Hidayati, Nanda; Jayadi, Jayadi; Utama, Angka; Mulyana, Dede (Eastasouth Institute, 2025)
This community service program aims to strengthen organizational culture, increase job satisfaction, and improve the performance of operational managers in Micro, Small, and Medium Enterprises (MSMEs). Using a qualitative empowerment approach, the program was implemented through a series of workshops and training sessions designed to develop leadership, communication, teamwork, and conflict resolution skills among MSME managers. Program participants, consisting of 25 operational managers from various sectors such as food processing, retail, and small-scale manufacturing, were selected based on their role in day-to-day operations and their potential to influence organizational culture. The program was evaluated through pre and post assessments, interviews, and observations, which showed significant improvements in organizational culture awareness, leadership skills, communication, and overall job satisfaction. Participants also demonstrated improved teamwork and problem-solving abilities. These improvements contributed to higher operational efficiency, which in turn improved business performance. These findings suggest that empowering operational managers with the necessary tools to create a positive work environment is key to the success and sustainability of MSMEs.